Identifying economic and societal drivers of engagement in agri-environmental schemes for English dairy producers. (February 2021) - Coyne, L; Kendall, H; Hansda, R; Reed, M.S.; Williams, D.J.L.
Highlights: This study identifies the economic and societal drivers of engagement in agri-environmental schemes by UK dairy producers. The use of a mixed-methodology allowed for an in-depth and detailed exploration of farmer behaviours. The paper focused on the role of agri-environmental schemes on the future resilience of the dairy sector. The study results will enable targeted policy development. Improving communication and engagement with farmers will ensure greater levels of engagement with agri-environmental schemes. Abstract: Livestock production is under increasing scrutiny regarding its impacts on the environment and its wider role in climate change. Consequently, there are a growing number of private agri-environmental schemes (AES) now operating alongside public AES that offer farmers economic rewards to maintain and enhance the environment. This study focused exclusively on a small number of commercial dairy producers located in the North West of England who were all suppliers of a global food producer and members of the producer's own private AES. The study explored the economic and societal drivers of adoption of agri-environmental behaviours and perceptions of the private processor AES. The study adopted a mixed-method approach. In Stage 1 a structured questionnaire was used to explore the role of an AES offered by the global food processor in the financial stability and environmental sustainability of dairy farms (n = 20). The survey sought to understand the range of interventions adopted, explore future adoption intentions and identify possible ways in which AESs could be extended. The results from the questionnaire were explored further in Stage 2, through qualitative in-depth interviews (n = 12). A thematic analysis approach was taken to describe the key themes that motivated farmer engagement in agri-environmental schemes. Overall, farmers felt that income from the private AES provided stability and resilience to their businesses, permitting them to have greater confidence in business planning and budgeting for the upcoming year. The majority of the farmers were not part of a public AES, but were already undertaking some agri-environmental behaviours and were motivated to join the private scheme primarily by financial incentives and by a desire to maintain the natural environment. A minority of respondents identified that the financial incentives offered had directly motivated a behaviour change. Decisions over which agri-environmental behaviours to adopt were driven by the existing animal management practices, geography and landscape of the farm. Farmers compared the private scheme favourably to available public AESs, which they perceived as more restrictive and providing insufficient reward for the "red tape" involved. In contrast, private scheme membership was perceived to have been beneficial for both their farm business and the local environment, and many reported personal satisfaction from engagement in agri-environmental behaviours. It is important that the design of future public AES does not "crowd out" private schemes, giving farmers increasing AES choice and increasing the overall amount of funding available for the delivery of public goods from agriculture.